Moral judgement by the disconnected left and right cerebral hemispheres: a split-brain investigation - Steckler, Conor M. (R Soc Open Sci, 2017)
Owing to the hemispheric isolation resulting from a severed corpus callosum, research on split-brain patients can help elucidate the brain regions necessary and sufficient for moral judgement. Notably, typically developing adults heavily weight the intentions underlying others' moral actions, placing greater importance on valenced intentions versus outcomes when assigning praise and blame. Prioritization of intent in moral judgements may depend on neural activity in the right hemisphere's temporoparietal junction, an area implicated in reasoning about mental states. To date, split-brain research has found that the right hemisphere is necessary for intent-based moral judgement. When testing the left hemisphere using linguistically based moral vignettes, split-brain patients evaluate actions based on outcomes, not intentions. Because the right hemisphere has limited language ability relative to the left, and morality paradigms to date have involved significant linguistic demands, it is currently unknown whether the right hemisphere alone generates intent-based judgements. Here we use nonlinguistic morality plays with split-brain patient J.W. to examine the moral judgements of the disconnected right hemisphere, demonstrating a clear focus on intent. This finding indicates that the right hemisphere is not only necessary but also sufficient for intent-based moral judgement, advancing research into the neural systems supporting the moral sense.